Bank efficiency and non-performing loans: Evidence from Malaysia and Singapore - Karim, M.Z.A.; Chan, Sok Gee; Hassan, S. (Univ Economics-Prague, 2010)
The objective of this paper is to investigate the relationship between non-performing loans and bank efficiency in Malaysia and Singapore. To achieve the objective, cost efficiency was estimated using the stochastic cost frontier approach assuming normal-gamma efficiency distribution model proposed by Greene (1990). The cost efficiency scores were then used in the second stage Tobit simultaneous equation regression to determine the effect of non-performing loans on bank efficiency. The results indicate that there is no significant difference in cost efficiency between banks in Singapore and Malaysia although banks in Singapore exhibit a higher average cost efficiency score. The Tobit simultaneous equation regression results clearly indicate that higher non-performing loan reduces cost efficiency. Likewise, lower cost efficiency increases non-performing loans. The result also support the hypothesis of bad management proposed by Berger and De Young (1992) that poor management in the banking institutions results in bad quality loans, and therefore, escalates the level of non-performing loans.